Refrigerating systems : CIBSE commissioning code R - Welch, Terry (CIBSE commissioning code ;, 2002)
Presents recommendations and guidance on current standards of good commissioning practice. Deals with the work involved in the commissioning of refrigerating plant used in air conditioning installations in buildings.